Pengaruh Fermentasi Dan Kondisi Penggarangan Terhadap Rendemen Lemak - Grecia Maharani (Jurnal Kimia dan Kemasan, 1997)
Cocoa butter is a vegetable fat obtained from cocoa beans, by hydraulic or expeller pressing, and by solvent extraction. This research studies the influence of the fermented and unfermented cocoa beans, and the effect of the fermented and the contents of fat. The conclussion of this research has shown that the fermentation process of cocoa beans doesn't influence fat content, and tempering at 7 5 °C withinn 24 hours shows a good result. Stan.dar Nasional Indonesia (SN!) N0.01-3748-1995 was used as a guideline to test quality of the fat.